A Study of Female Characters in Diaspora Literature with Special Reference to Select Works of Meena Alexander and Chitra Banerjee - Asha L. Bavarava (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2021)
Meena Alexander returned to India in the 1970s to teach at the university in Hyderabad. The author makes a reference to the origin of Nampally Road in her autobiography Fault Lines. As the title of the memoir indicates, her sense of displacement or dislocation is such a strong sentiment, owing perhaps to the physical path of her life that she appears to struggle with lines, boundaries and environments in her work and self. This universal sense of displacement is evidenced in Nampally Road, where much like the author, the main character Mira Kannadical returns with much optimism to make a new beginning in her homeland, extremely disaffected after her four‐year study stint in England. Mira’s return coincides with preparations for the festivities surrounding the 60th birthday celebrations of Limca Gowda, the Chief Minister of Andhra Pradesh.